COVID‐19 and Headache Medicine: A Narrative Review of Non‐Steroidal Anti‐Inflammatory Drug (NSAID) and Corticosteroid Use. Issue 8 (10th July 2020) - Arca, Karissa N.; Smith, Jonathan H.; Chiang, Chia‐Chun; Starling, Amaal J.; Robertson, Carrie E.; Halker Singh, Rashmi B.; Schwedt, Todd J.; Kissoon, Narayan R.; Garza, Ivan; Rozen, Todd D.; Boes, Christoper J.; Whealy, Mark A.; et al.
Abstract : Objective: To summarize the current literature on non‐steroidal anti‐inflammatory drug and corticosteroid use during the coronavirus disease 2019 (COVID‐19) pandemic, recognizing that these are commonly used treatments in the field of headache medicine. Background: The use of non‐steroidal anti‐inflammatory drugs and corticosteroids in patients during the COVID‐19 pandemic has been a controversial topic within the medical community and international and national health organizations. Lay press and social media outlets have circulated opinions on this topic despite the fact that the evidence for or against the use of these medications is sparse. In the field of headache medicine, these medications are used commonly and both patients and clinicians may have questions or hesitations pertaining to their use during the COVID‐19 pandemic. Methods: A detailed search of the scientific and popular literature was performed. Results: There is limited literature pertaining to the safety of non‐steroidal anti‐inflammatory drugs and corticosteroids during the COVID‐19 pandemic. To date, there are no clear scientific data that preclude the use of non‐steroidal anti‐inflammatory drugs in the general population who may acquire COVID‐19 or in those acutely infected with the virus. Several health organizations have concluded that treatment with corticosteroids during active infection should be avoided due to concerns of prolonged viral shedding in the respiratory tract and the lack of survival benefit based on the data from past coronaviruses and influenza virus; specific exceptions exist including treatment for underlying asthma or chronic obstructive pulmonary disease, septic shock, and acute respiratory distress syndrome. Conclusion: Scientific information regarding the COVID‐19 pandemic is constantly evolving, and limited or contradictory information can lead to confusion for both patients and clinicians. It is recommended that prior to prescribing non‐steroidal anti‐inflammatory drugs and steroids for the treatment of headache, clinicians have open discussions with their patients about the potential risks and benefits of using these medications during the COVID‐19 pandemic. This manuscript summarizes the currently available evidence and understanding about these risks and benefits to help clinicians navigate such discussions.